Molecular breeding in wheat, maize and sorghum strategies for improving abiotic stress tolerance and yield - Hossain, Mohammad Anwar; Alam, Mobashwer; Seneweera, Saman; Rakshit, Sujay; Henry, Robert J (CAB International, 2021)
"This book covers the latest understanding of molecular and genetic bases of abiotic stress tolerance and yield improvement of wheat, maize and sorghum, to develop strategies for improved stress tolerance and enhanced crop productivity"--